1983
DOI: 10.1180/minmag.1983.047.343.01
|View full text |Cite
|
Sign up to set email alerts
|

Thermal aspects of the origin of Hebridean Tertiary acid magmas. II. Experimental melting behaviour of the granites at 1 kbar PH20

Abstract: ABSTRACT. Experimental melting equilibria at 1 kbar PH2O are reported for three early Tertiary granites from Skye and one from Rhum, together with a quartz rnonzonite from Ardnamurchan. The Hebridean Province leucogranites show cotectic melting behaviour, whilst associated 'primitive' (mostly adamellitic) acid plutons have silicate liquidi N 925 ~ and plagiodase liquidi ~ 875 ~ At such high temperatures the morefusible crustal rock types of the region would be almost completely molten. If the Tertiary 'primiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In the primitive mantle-normalized multi-element patterns, except for four drill samples (ZK05-25.4, ZK05-36.5, ZK03-24.4, and ZK03-29.1), all samples show Thompson (1983) and Thompson et al (2001). Arrows point in the direction of decreasing temperature.…”
Section: R E S U Lt S 40 Ar/ 39 Ar Age Datamentioning
confidence: 99%
“…In the primitive mantle-normalized multi-element patterns, except for four drill samples (ZK05-25.4, ZK05-36.5, ZK03-24.4, and ZK03-29.1), all samples show Thompson (1983) and Thompson et al (2001). Arrows point in the direction of decreasing temperature.…”
Section: R E S U Lt S 40 Ar/ 39 Ar Age Datamentioning
confidence: 99%
“…The results show that 5-30% partial melting followed by $30-50% fractionation might be the most likely process to generate the group 3 rhyolites could then induce the melting of the underplating mafic rocks hybridized with crustal materials to form the group 3 A-type magma at shallower levels. Experimental work has demonstrated that the mineral assemblage of A-type magma can only be produced in high temperature environments (>900°C) with low H 2 O contents (Clements and Vielzeuf 1987;Thompson 1983). This suggests that the group 3 rocks represent highly fractionated products from high-temperature and relatively anhydrous magmas.…”
Section: Group 3 Rhyolites: Melting Of a Hybridized Source And Subseqmentioning
confidence: 96%
“…An EMII-type source is generally characterized by 87 Sr/ 86 Sr ratios in excess of 0.7065 and intermediate 143 Nd/ 144 Nd ratios (Hart 1988;Weaver 1991). It has lower Ba/Nb and Ba/La ratios, but higher Th/La and Zr/Nb ratios, than those of an EMI-type mantle source (Hart 1988;Thompson 1983;Palacz and Saunders 1986;Weaver 1991). The group 1 rocks have 87 Sr/ 86 Sr ratio of 0.70602 $ 0.70812, Nd (t) value=À1.63 to +0.11, Nb/La=0.64-0.99 and Zr/Nb=4.43-9.07, displaying an affinity to an EMII-like source (Fig.…”
Section: Source Heterogeneitymentioning
confidence: 97%
“…The geochemical work of Walsh (1975) and Walsh & Henderson (1977) supports this conclusion to some extent, as they suggested that the tonalite was derived from country-rock contamination rather than fractional crystallization of the gabbros. Thompson (1983) carried out melting experiments on a sample of the inner 'quartz monzonite' part of the intrusion (3h on Fig. 1) at 1 kbar H 2 O and showed that its liquidus temperature was in excess of 1020 • C. This led him to conclude that the petrogenesis of the quartz monzonite must have involved a combination of both crustal contamination and fractional crystallization.…”
Section: D Magma Mixing At the Intrusion Roof-zonementioning
confidence: 99%
“…1) has been accorded some significance as the most areally extensive intermediate (in composition) intrusion in the British Palaeogene Igneous Province (e.g. Richey & Thomas, 1930; Thompson, 1983). Contact information with the surrounding quartz gabbro and laminated gabbro is poor, but along its southern margin a steeply outward-dipping (79°SE) intrusive contact toward the laminated gabbro is observed (NM 47523 68048) (fig.…”
Section: Lithological Relationships and Other Field Observationsmentioning
confidence: 99%